E-commerce: Determining factors and the importance of the e-trust - Fernando Fernández-Bonilla (International Telecommunications Society (ITS), 2020)
This paper studies how to calculate the propensity of individuals to participate in e-commerce, studying the variables that affect costumers at the time of the online transactions and how to modify their inclination to it, being the most relevant variables socioeconomic and those which are related to the personal abilities of individuals, being one of the most important the e-Trust, variable of special importance in this business and that influences not only on buying or not, but also on how they relate to the bidders. In order to do this study, a Logit model is used.
Keywords: C01; C25; D12; L81; L86; 330; e-commerce; e-trust; Internet; Logit; consumers